2017
DOI: 10.1038/tpj.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic module associations with pathogenesis: a network-based approach to understanding drug toxicity

Abstract: Despite investment in toxicogenomics, nonclinical safety studies are still used to predict clinical liabilities for new drug candidates. Network-based approaches for genomic analysis help overcome challenges with whole-genome transcriptional profiling using limited numbers of treatments for phenotypes of interest. Herein, we apply co-expression network analysis to safety assessment using rat liver gene expression data to define 415 modules, exhibiting unique transcriptional control, organized in a visual repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(137 citation statements)
references
References 70 publications
3
133
0
Order By: Relevance
“…Notably scoring of the modules using the Nextbio Body Atlas (Data not shown) reveals that genes in all four modules are over expressed in inflammatory cells including the blood, suggesting that what may be being detected are transcripts from inflammatory infiltrates that manifest following tissue damage. Notably this is consistent with observations that co-regulation modules in the liver are related, in part to changes in cellularity (i.e., increases or decreases in certain cell types; Sutherland et al, 2017 ). Chemicals that act through a receptor have cascades of signaling that often attenuate cell death by inhibiting apoptosis (Mally and Chipman, 2002 ) therefore decreasing cell turnover.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably scoring of the modules using the Nextbio Body Atlas (Data not shown) reveals that genes in all four modules are over expressed in inflammatory cells including the blood, suggesting that what may be being detected are transcripts from inflammatory infiltrates that manifest following tissue damage. Notably this is consistent with observations that co-regulation modules in the liver are related, in part to changes in cellularity (i.e., increases or decreases in certain cell types; Sutherland et al, 2017 ). Chemicals that act through a receptor have cascades of signaling that often attenuate cell death by inhibiting apoptosis (Mally and Chipman, 2002 ) therefore decreasing cell turnover.…”
Section: Discussionsupporting
confidence: 91%
“…The approach uses transformations of the correlation between co-expressed genes to reveal interconnectedness amongst gene network nodes and permutation procedures to identify statistically significant gene network modules that overlap between sample conditions (Langfelder et al, 2011 ). Recent utilization of WGCNA on rat liver gene expression data from drug toxicity studies revealed 415 gene network models that associate with mechanisms of liver pathogenesis (Sutherland et al, 2017 ). We used the WGCNA approach to reconstruct gene networks using microarray gene expression data from male rat livers and identify preserved modules between chemicals that exert their MOA through receptors (RM) vs. those that are non-receptor-mediated (NRM).…”
Section: Introductionmentioning
confidence: 99%
“…Gene co-expression network analysis is a systems biology method used to describe the correlation patterns among genes across different experimental samples. It allows representing, investigating and understanding the complex molecular interactions within the exposed system [22,45]. The genes and their interactions are represented as a network (or graph) where the genes are the nodes of the network and their strength of similarity is represented as weighted edges between the nodes [46].…”
Section: Gene Co-expression Network Analysismentioning
confidence: 99%
“…Subsequently, they ranked the genes in the network by computing different topological measures, identified and functionally characterized a set of genes that play a key role in the adaptation to exposure. Other approaches focus on identifying gene network modules associated with specific patterns of drug toxicity [45].…”
Section: Gene Co-expression Network Analysismentioning
confidence: 99%
See 1 more Smart Citation